Manuel Mujica Láinez, Lucio V. López, Horacio Quiroga, Georges Clemenceau, Carlos Martínez Moreno, Roberto Arlt, Enrique González Tuñón, César Fernández Moreno, Juan José Sebreli, Bernardo Kordon, Miguel Brascó, José María Salaverría: Crónicas de Buenos Aires. Edic. Jorge Álvarez, 1965, 154 páginas. - Polimeni, Dante Osvaldo (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía Argentina y Americana, 1966)

(untitled)
Fil: Polimeni, Dante Osvaldo.